2017
DOI: 10.4103/ijmr.ijmr_651_15
|View full text |Cite
|
Sign up to set email alerts
|

Fly ash-based water dispersible powder formulation of Bacillus thuringiensis var. israelensis: Development & laboratory evaluation against mosquito immatures

Abstract: Background & objectives:Bacillus thuringiensis var. israelensis (Bti) formulations are presently being used for insect control. In this study, a water dispersible powder (WDP) formulation using fly ash (FA) as a carrier material was developed and studied for its activity against the larval stages of major mosquito vector species.Methods:An indigenous isolate Bti (Vector Control Research Centre B17) was mass produced using a 100 l fermentor in soya-based medium. The bacterial biomass was mixed with lignite FA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…aegypti are unlikely to arise resistant to Bti (PÉREZ et al, 2005;SOBERÓN et al, 2018). In addition, these proteins are specific to their target, There are a variety of Bti-based formulations in both liquid and granular form (TAMILSELVAN et al, 2017;SHANKAR et al, 2019), containing crystals with insecticidal activity and viable spores that assist the bacterium's recycling process (BECKER, 2000;MELO-SANTOS et al, 2009). The recycling capacity of Bti can be influenced by environmental conditions, such as: direct exposure to sunlight, ultraviolet radiation and rains that directly affect the efficiency of the biolarvicide (IGNOFFO et al, 1981;PUSZTAI et al, 1991;MYASNIK et al, 2001;ALVES, LECUONA, 1998;MELO-SANTOS et al, 2009;LIMA et al, 2016;ZHANG et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…aegypti are unlikely to arise resistant to Bti (PÉREZ et al, 2005;SOBERÓN et al, 2018). In addition, these proteins are specific to their target, There are a variety of Bti-based formulations in both liquid and granular form (TAMILSELVAN et al, 2017;SHANKAR et al, 2019), containing crystals with insecticidal activity and viable spores that assist the bacterium's recycling process (BECKER, 2000;MELO-SANTOS et al, 2009). The recycling capacity of Bti can be influenced by environmental conditions, such as: direct exposure to sunlight, ultraviolet radiation and rains that directly affect the efficiency of the biolarvicide (IGNOFFO et al, 1981;PUSZTAI et al, 1991;MYASNIK et al, 2001;ALVES, LECUONA, 1998;MELO-SANTOS et al, 2009;LIMA et al, 2016;ZHANG et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Indian fly ash has very low radioactivity and heavy metal count 30 . Analysis of the shortlisted formulation by Tamilselvam et al 23 also revealed the presence of only micro- and macronutrients and absence of any kind of heavy metals. This formulation has also shown safety against non-target organisms and mammalian systems.…”
mentioning
confidence: 97%
“…Charcoal and plaster of Paris are some of the common carrier material for Bt formulations. Tamilselvam et al 23 in this issue have reported a new carrier material fly ash as an alternative to the common carrier powder-based Bti formulation. Use of fly ash as a carrier in insecticides is generally known.…”
mentioning
confidence: 99%
See 1 more Smart Citation